Bilateral septic arthritis of the shoulder: case report and literature review - Maia, Roberto Barreto; Silva, Lucas Fraga Cunha da; Santos, Herbert Nascimento dos; Andrade, Fernando Antônio Batista; Matos, Marcos Antônio Almeida; Barros, Rogério Meira; Santos, Marcus Vinícius Silva; Alves Rezende, Luis Guilherme Rosifini (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Bilateral shoulder septic arthritis is a rare condition in immunocompetent patients without known risk factors, therefore, it can be easily misdiagnosed. Septic arthritis is an emergency due to its potential to cause rapid destruction of cartilage and bone as well as the risk for systemic spread. Aggressive early treatment is crucial for easing pain, preventing joint collapse, and permanent loss of shoulder function. We presented a case report of a 68 years-old man, suffering from multiple comorbidities and bilateral shoulder septic arthritis. The patient underwent arthroscopic surgery in the left shoulder. Antibiotic therapy was carried out after the surgical procedure using clindamycin. The patient had a satisfactory outcome, characterized by regression of the inflammatory symptoms in both shoulders. There was an improvement in pain and fevers settled. In this case report, we have also discussed treatment options as well as possible outcomes.